FEED CONSUMPTIONS AND BLOOD METABOLITE LEVELS OF PE DOES FED WITH SILAGES AT LATE PREGNANCY - E., KURNIAWAN; DOLOKSARIBU, L.; DEWANTARI, M.; MAHARDIKA, I G. (Majalah Ilmiah Peternakan; Vol 28 No 1 (2025): Vol. 28 No. 1 (2025), 2025)
Productivity of PE goats in Indonesia was relatively low due to the limited availability of quality feed, and lack of farmers’ knowledge about feeding management. Utilizing waste of soybean husk from tempe-making and bre- wer’s spent grain from brewing industry provides economical quality feeds throughout the year. This study was to determine effect of feeding soybean husk silage (SHS), brewer’s spent grain silage (BSGS), and odot silage (OS) at the fifth month of pregnancy to day-60 post-partum on variables observed: total feed consumption, and blood metabolite levels of PE does. The study was conducted from July to October 2023 in Lemukih Village, Bali; using randomized block design consisting of four feeding treatments (T): Forage (T0), Forage+SHS (T1), Forage+BSGS (T2), and Forage+OS (T3). The results indicated that daily SHS consumption was the highest 7.194 ± 74.2 g/day with their total feed consumption 647.5 ± 26.6 kg. The highest blood glucose level was 45.91 ± 2.3 mg/dl at 06:00 hours post-feeding, albumin was 4.80 ± 0.65 g/dl at 03:00 hours post-feeding and total protein was 8.78 ± 0.2 g/dl at 00:00 hour post-feeding. Feeding forage+SHS (T1) to PE goats increased feed consumption with normal blood metabolites levels without interference with their health status.